Stochasticity-dominated rare fungal endophytes contribute to coexistence stability and saponin accumulation in Panax species - Ye Liu; Liping Shi; Fei Hong; Guangfei Wei; Zhenzhen Jiang; Xiuye Wei; Jingjing Peng; Guozhuang Zhang; Linlin Dong (Environmental Microbiome)
Abstract Fungal communities inhabiting plant tissues are complex systems of inter-species interactions, consisting of both the “abundant biosphere” and “rare biosphere”. However, the composition, assembly, and stability of these subcommunities, as well as their contributions to productivity remain unclear. In this study, the taxonomic and functional composition, co-occurrence, and ecological assembly of abundant and rare fungal subcommunities in different tissues of three Panax species were investigated. Abundant subcommunities were dominated by potential plant pathogens belonging to Microbotryomycetes, while saprotrophic fungi like Agaricomycetes and Mortierellomycetes were more prevalent in rare subcommunities. The rare taxa played a central role in upholding the stability of the fungal networks as driven by Dothideomycetes and Sordariomycetes. Homogeneous selection played a larger role in the assembly of abundant fungal subcommunities compared to the rare counterparts, which was more dominated by stochastically ecological drift in all plant species. Rare biospheres played a larger role in the accumulation of saponin compared to their abundant counterparts, especially in the leaf endosphere, which was mainly affected by environmental factors (Mg, pH, OC, and etc.). Furthermore, we found that rare species belonging to unidentified saprotrophs were associated with saponin formation. This study provides hypotheses for future experiments to understand mechanisms accounting for the variations in the composition and function of rare fungal subcommunities across different Panax species.